If it's not what You are looking for type in the equation solver your own equation and let us solve it.
D( x )
x = 0
x = 0
x = 0
x in (-oo:0) U (0:+oo)
3/x-(2/y) = 0
3/x-2*y^-1 = 0
3*x^-1 = -(-2*y^-1) // : 3
x^-1 = (2*y^-1)/3
-1 < 0
1/(x^1) = (2*y^-1)/3 // * x^1
1 = x^1*((2*y^-1)/3) // : (2*y^-1)/3
(3*y)/2 = x^1
x = (3*y)/2
x = (3*y)/2
| .25x^2+x=-1 | | 13x-4=12x-6 | | 5x+1=2.2 | | 112-15=b | | 13x-7=5x-47 | | 12x+10=5x+24 | | 3x-12=9x-72 | | 9x+4=5.8 | | S/6-12=-16 | | 2+r=5 | | 3.3x+5.7y-6.7=0 | | 4x-11=10x-11 | | 4.25x+3=-3x^2 | | 3x+5=10x-30 | | (3.5x)+x=100 | | √8/21 | | 13x-9=8x-34A-5B-4C-2D-7E-1 | | 7x-11=8x-14 | | X-18y=45 | | F(xy)=2x^2+3xy+4y^2-5x+2y | | 4x+7=12x-33 | | 5x+12=4x+12 | | -2=-.6(4/x) | | 7x-2/3=3 | | -2=-0.6(4/x) | | 9x+12=4x+62 | | 7n^2+9=-123 | | 2y=43-17 | | 4x+9=5x+6 | | 6(x)-y=9 | | -4x^2+6=2x | | 14x+12=3x+78 |